Management of Resorbed Mandibular Ridge with Neutral Zone Technique: A Case Report - Sharma, Rinu; Mathema, S.; Pathak, B. (Journal of Nepalese Prosthodontic Society, 2018)
Patients with resorbed mandibular ridge poses a challenge for prosthodontic rehabilitation. The ongoing diminution of denture foundation defies the basic mechanism of denture stability and support. The technique of neutral zone to construct a denture that is shaped by muscle function and is in harmony with the surrounding oral structures can remarkably improve prognosis of such patients. The neutral zone is the area in the oral cavity where during function; the forces of the cheeks and lips pressing inward neutralize the forces of the tongue pressing outward. Thus physiologically optimal teeth arrangement and harmonious denture contours and can be achieved to maximize prosthesis stability, comfort, and function for patients.This clinical report describes rehabilitation of a patient with severely resorbed mandibular ridge using neutral zone impression technique.